Consumer behavior and food prices during the COVID‐19 pandemic: Evidence from Chinese cities. (20th January 2022) - Yang, Bixuan; Asche, Frank; Li, Tao
Abstract: We find that Chinese consumers responded strongly to government restrictions during the COVID‐19 crisis. Our event‐study framework shows that emergency declarations raised average food prices by as much as 7.8 standard deviations of the price change distribution, with a much larger effect on non‐perishable vegetable prices (e.g., 17.0 standard deviations for Chinese cabbage prices). The effects of lockdowns were smaller but longer‐lasting. These results suggest that consumers panic bought non‐perishables under emergency declarations while under lockdowns there was a sustained increase in demand for non‐perishables. Such consumer behavior likely caused sizable losses in consumer welfare, especially among poor households.